Problematika Guru dalam Mengintegrasikan Pembelajaran Biologi dengan Islam Di Madrasah Aliyah Negeri: Literatur Review - Siti Sahara; Ardi Ardi (LP2M UIN Ambon, 2025)
This study discusses the challenges faced by teachers in integrating Biology learning with Islam in State Islamic Senior High Schools (Madrasah Aliyah Negeri), encompassing conceptual, pedagogical, and structural difficulties and challenges. The study aims to systematically examine the forms, sources, and characteristics of these challenges through a literature review. The research design employed a Systematic Literature Review (SLR) with the stages of searching, selecting, and reviewing accredited scientific articles. Data sources were obtained from Indonesian and English articles on Google Scholar (2019–2026) relevant to the integration of Biology and Islam. Content analysis was conducted on eight articles that met the criteria, resulting in findings that challenges faced by teachers in integrating Biology learning with Islam include limited integrated teaching materials, uneven pedagogical and interdisciplinary scientific competencies, curriculum and learning resource constraints, and limited structural support. This study is expected to serve as a reference for developing Biology learning that is more integrated with Islam in State Islamic Senior High Schools (Madrasah Aliyah Negeri).